Variance of Rates and Costs of Unplanned Readmissions in Tertiary Hospitals in South Korea (Medico Legal Update, 2019)
This study attempted to estimate rates and costs of unplanned readmissions of high level hospitals Korea.Unplanned readmissions are used as a proxy of the quality of medical services. Korean Health Insurancereimburses tertiary hospitals 5% more fees than general hospitals. The gaps of the health insurancereimbursement rates are not based on the difference in quality of medical services among the level ofhospitals. It needs to be reviewed whether the gaps are reflecting difference of the quality of medical services.The Health Insurance Claims Data of patients readmitted within 28 days after discharge from tertiaryhospitals in 2014 were classified into unplanned claims. Unplanned readmissions were compared withplanned readmissions.The risk-adjusted average readmission rate was 6.4% in all tertiary hospitals, but 5.7% in general hospitalswith 500 beds or more. Coefficient of variance (CV) of readmission rate was higher in tertiary hospitals(32.8) than general hospitals with 500 beds or more (17.5). However, there was no significant difference inmean medical fees per unplanned readmission between two groups of hospitals. It was 3,810 Won in thetertiary hospitals and 3,834 Won in general hospitals with 500 beds or more.The findings of this study showed that higher costs did not necessarily yield higher quality of care, suggestingthat quality control measures should be required to reduce unplanned readmissions in tertiary hospitals.